Recruitment and retention of underrepresented populations in Alzheimer's disease research: A systematic review - Andrea L. Gilmore‐Bykovskyi; Yuanyuan Jin; Carey Gleason; Susan Flowers‐Benton; Laura M. Block; Peggye Dilworth‐Anderson; Lisa L. Barnes; Manish N. Shah; Megan Zuelsdorff (Alzheimer’s & Dementia: Translational Research & Clinical Interventions)
Abstract Introduction Alzheimer's disease and related dementias (ADRD) disproportionately impact racial and ethnic minority and socioeconomically disadvantaged adults. Yet, these populations are significantly underrepresented in research. Methods We systematically reviewed the literature for published reports describing recruitment and retention of individuals from underrepresented backgrounds in ADRD research or underrepresented participants' perspectives regarding ADRD research participation. Relevant evidence was synthesized and evaluated for quality. Results We identified 22 eligible studies. Seven studies focused on recruitment/retention approaches, all of which included multifaceted efforts and at least one community outreach component. There was considerable heterogeneity in approaches used, specific activities and strategies, outcome measurement, and conclusions regarding effectiveness. Despite limited use of prospective evaluation strategies, most authors reported improvements in diverse representation in ADRD cohorts. Studies evaluating participant views focused largely on predetermined explanations of participation including attitudes, barriers/facilitators, education, trust, and religiosity. Across all studies, the strength of evidence was low. Discussion Overall, the quantity and quality of available evidence to inform best practices in recruitment, retention, and inclusion of underrepresented populations in ADRD research are low. Further efforts to systematically evaluate the success of existing and emergent approaches will require improved methodological standards and uniform measures for evaluating recruitment, participation, and inclusivity.